Long-term experiments in agricultural and ecological sciences - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Long-term experiments in agricultural and ecological sciences edited by R A Leigh and A E Johnson 1994 448pp ISBN 085198 933 0 price UKL 55.00 CAB Intemational Wallingford, Oxon OX10 8DE, UK